Learn ASP.NET MVC and Entity Framework (Database First) - Williams, Trevoir (Packt Publishing, 2020)
Master the fundamentals of ASP.NET MVC and Entity Framework by building a small school management system About This Video Learn how to build a fully data-driven web application Get a solid understanding of the .NET MVC application development flow Discover how to manage packages in a .NET project like a pro In Detail NET, known for its proven scalability, reliability, and support, is the most widely used programming language today. It can handle almost any problem related to desktop to mobile to dynamic web applications. This video course will teach you the ASP.NET Model View Controller (MVC) development to make you one of the most in-demand programmers. The course starts with the installation of Visual Studio and prepares you to create a web application for learning the process of ASP.NET MVC web development. You will learn to explore the MVC folder structure, set up a database, create Entity Framework models from the database tables, and add controller and views. Moving along, you will learn to implement user authentication by adding user data points, controlling user access, and adding roles and authorizations. Finally, you will understand package management and learn to work with jQuery, jQuery UI, and Ajax. By the end of this course, you will have become familiar with the fundamentals of ASP.NET MVC and Entity Framework and have developed the skills you need to create a data-driven web application.
Online resource; Title from title screen (viewed November 30, 2020)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos